Prática de ensino supervisionada em Educação Pré-Escolar e Ensino do 1º Ciclo do Ensino Básico - Ribeiro, Filipa Leite (2013)
O presente relatório foi realizado no âmbito da Unidade Curricular de Prática de Ensino Supervisionada, do Mestrado Pré-Escolar e do Ensino do1.º Ciclo do Ensino Básico. A Prática de Ensino Supervisionada foi desenvolvida com um grupo de crianças de três e quatro anos de idade em Educação Pré-Escolar e com um grupo de crianças de sete e oito anos de idade do 1.º Ciclo do Ensino Básico. No relatório abordamos a contextualização das instituições, a caraterização dos grupos bem como a descrição das experiências de aprendizagem desenvolvidas nos dois contextos. Procuramos promover experiências que fossem significativas, integradoras e socializadoras. Tentamos sempre ter em atenção os interesses das crianças, bem como, a sua participação ativa no decorrer de toda a ação educativa. The present report has been carried out within the Curricular unit Supervised Teaching Practice, integrated in Master's Degree Preschool and the school first cycle of Basic Education. The Teaching Practice Supervised was developed with a group of children of three and four years old in Preschool Education and with a group of children of seven and eight years of age for the 1st cycle of Basic Education. In the report we address the context of the institutions, the characterization of the groups as well as the description of learning developed experiences in the two contexts. We seek to promote experiences with significant learning, integrative and socializing. Always try to keep in mind the interests of children, as well as their active participation in the course of all the education action. The learning experiences made are presented in descriptive and reflective way and seek to document the curricular integration held throughout the educational process. Also in this document are present the photographic records and speeches of children that help sustain the action developed. Este trabalho tem como principal objetivo caraterizar a investigação realizada na década 2000-2010 em todos os estabelecimentos de ensino superior público português no âmbito da Tecnologia Educativa. Recorrendo à metodologia de estudo analítico procurou-se obter a resposta para esta questão de investigação. Com base no acesso aos trabalhos de investigação procedeu-se à criação de uma grelha quantitativa com variáveis multi-exclusivas de registo de dados, de acordo com os objetivos da investigação. Após tratamento dos dados recolhidos e registados, foi possível verificar que o número de trabalhos apresentou um aumento substancial, especialmente na segunda metade da década em estudo. As instituições de ensino superior que apresentam o maior número de trabalhos neste âmbito são as Universidades do Minho, Aveiro e Porto. Grande parte dos trabalhos são análises empíricas que têm a sua origem na procura de resolução de problemas no ensino, especialmente no terceiro ciclo e na disciplina de matemática. A metodologia mais utilizada pelos investigadores é o estudo de caso. As variáveis das áreas temáticas constantes na grelha de registo de dados foram agrupadas em função dos 3 eixos de ação do Plano Tecnológico da Educação, concluindo-se que a maioria dos trabalhos se enquadra no eixo Conteúdos. Conscientes de que os três pilares da sociedade da informação e do conhecimento são a tecnologia, formação e conteúdos e que este último foi descurado na primeira metade da década 2000-2010, estamos convictos de que a investigação em Tecnologia Educativa tem vindo a contribuir significativamente para minimizar as barreiras ao nível dos conteúdos e objetos de aprendizagem, que até há bem pouco tempo atrás foram negligenciadas.The evolution of information and knowledge society creates new challenges to the education system. Successive governments have taken steps, have created projects and programs in order to meet the new challenges of this society that emerges. The Educational Technology has come to prominence in Sciences Education, while postgraduate courses are emerging and increasing in number, contributing to the growth of scientific production in Educational Technology. This work has as main objective to characterize the research carried out in the decade 2000-2010, in all Portuguese public institutions of higher education, in the field of Educational Technology. Using an analytical study methodology we tried to obtain the answer to this question of the research. Based on access to the research work we proceeded to create a quantitative grid with multi-exclusive variables of data record, in accordance with the objectives of the investigation. After processing the collected and recorded data, it was possible to verify that the number of works had increased substantially, especially in the second half of the decade under study. The higher education institutions that have the greatest number of works in this area are the University of Minho, University of Aveiro and University of Oporto. Most studies are empirical analyzes that have their origin in the search of solving problems in education, especially in the third cycle and in the subject of mathematics. The methodology most used by most researchers is the case study. The variables of the subject areas listed in the grid of data record were grouped according to the three action axes of the Education Technological Plan, concluding that the most of the work fits into the Contents axis. Being aware that the three pillars of the information and knowledge society are technology, training and contents, and that the latter was overlooked in the first half of the decade 2000-2010, we believe that research in Educational Technology has contributed significantly to minimize barriers in terms of content and learning objects, that until very recently were neglected.